Pengembangan Media Pipa Puzzle untuk Meningkatkan Kreativitas Belajar Siswa pada Mata Pelajaran Matematika Materi Bangun Ruang Kelas VI SD PAB 23 Medan - Aulya, Tiara Khairulisca Diva; Husna, Faisal (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research aims to develop Puzzle media to increase students' learning creativity in mathematics in spatial building material in Class VI of SD PAB 23 Medan. Observation results showed that 67.8% of students had low creativity and 57.1% of students felt bored in the learning process. The contributing factors are the lack of learning media and teachers who still focus on guidebooks. Therefore, researchers are interested in developing puzzle media with the Pipe Puzzle type to increase student creativity. Media development uses the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). This media is validated by media experts, material experts and teachers. The validation results show that this media is suitable for use with a percentage of 80% from media and material experts, and 94% from teachers and students. This research is expected to provide benefits for teachers, students, schools and researchers in improving the quality of education, enriching knowledge about innovative learning media, and increasing students' abilities in solving mathematical problems. Apart from that, this research can also help increase learning motivation, awareness of the importance of creativity, and develop students' critical thinking abilities. It is hoped that the research results can contribute to the development of innovative and effective mathematics learning media.